MODEL DAKWAH HIZBUT TAHRIR INDONESIA - Shobron, Sudarno (Muhammadiyah University Press, 2014)
The existence of Transnational Islam Movement, Hizbut Tahrir, to Indonesiaadds the number of Islam movement conveying dakwah (missionary endeavor) askingto do the good deed and avoiding bad ones. Each organization has its different strategyand model though it is possible that there is similarity. Hizbut Tahrir came to Indonesiain 1983 by offering radical changing agenda, that is, changing the Indonesian politicalsystem to Khilafah al-Islamiyah.The Islamic political system gets appreciation form a number of Islamic people whowant changes. There are two dakwah strategies, that is, cultural and structural. Thecultural is by changing the awareness of the society about the importance of changes inIndonesia with only one way that is establishing political system Khilafah al-Islamiyah.Structural strategy is carried out by forming opinion for Islamic people and peoplethough rallies and khilafah conferences. The way to make the awareness of Islamicpeople is by dakwah.The Hizbut Tahrir missionary endeavor follows the Prophet Muhammad (peace beupon him) in making changes in Mecca and Medina though three phases, that isdevelopment of cadres, interaction to society and authority.Kehadiran gerakan Islam transnasional, Hizbut Tahrir, ke Indonesiamenambah jumlah gerakan Islam yang melakukan dakwah amar makruf nahi munkar.Masing-masing organisasi memiliki stratgei dan model dakwah yang berbeda-bedawalaupun tidak menutup kemungkinan ada persamaannya. Hizbut Tahrir datang keIndonesia pada tahun 1983 dengan menawarkan agenda perubahan yang radikal, yaknimerubah sistem politik Indonesia dengan sistem Khilafah al-Islamiyah.Sistem politik Islam tersebut mendapat apresiasi dari sebagian umat Islam yangmenginginkan perubahan. Strategin dakwah yang dilakukan ada dua, yakni kulturaldan structural. Kultural dengan merubah kesadaran umat Islam akan pentingnyaperubahan Indonesia, satu-satunya adalah dengan menegakkan sistem politik Khilafahal-Islamiyah. Stratgi struktural yang dilakukan dengan membentuk opini publik umatIslam dan rakyat Indonesia melalui demonstrasi-demonstrasi, konferensi khilafah. Jalanyang diambil agar kesadaran umat Islam itu terbentuk adalah dengan dakwah.Model dakwah Hizbut Tahrir mengikuti cara Rasulullah saw dalam melakukanperubahan di Mekkah dan Madinah dengan tiga tahap, yakni tahap pembinaan danperkaderan, tahap berinteraksi dengan masyarakat, dan tahap penerimaan kekuasaan.Kata Kunci: khilafah al-Islamiyah; kultural dan struktural; perubahan radikal.